Novel allergens from ancient foods: Man e 5 from manioc (Manihot esculenta Crantz) cross reacts with Hev b 5 from latex. Issue 6 (25th March 2013) - Santos, Keity Souza; Gadermaier, Gabriele; Vejvar, Eva; Arcuri, Helen Andrade; Galvão, Clovis Eduardo; Yang, Ariana Campos; Resende, Virgínia Maria Ferreira; de, Carlo; Himly, Martin; Mari, Adriano; Liso, Marina; Pomponi, Debora; et al.
<x xml:space="preserve">Abstract</x> Scope Manioc (Manihot esculenta) is a tuber mainly consumed in the Southern Hemisphere and used worldwide by food and chemistry industry. We aimed to recombinantly produce and characterize the first manioc allergen and evaluate its IgE reactivity in sera of Brazilian and Italian patients. Methods and results The molecule, termed Man e5, was expressed in E. coli, characterized by amino acid analysis, mass spectrometry, circular dichroism, HPLC, and dynamic light scattering. A tertiary structural model of the protein was produced using bioinformatics and susceptibility to pepsin digestion was analyzed in vitro. Based on its high content of charged residues, heat stability, flexibility and lack of secondary structure elements, the allergen was determined a member of the intrinsically disordered protein family. Brazilian patients were selected based on manioc allergy and Italians based on latex allergy and sensitization to Hev b 5.71% of Brazilians and 40% of Italians were in vitro IgE positive to Man e5. Cross‐inhibition assays suggest a possible involvement of this allergen in the latex‐fruit syndrome. Conclusion Man e5, the first purified allergen from manioc demonstrates IgE cross‐reactivity with Hev b 5. Data suggest Hev b 5 might act as primary sensitizer and could therefore lead to allergic manifestations upon manioc consumption without prior exposition.